FENOMENA GLASS CEILING PADA INDUSTRI KONSTRUKSI : STUDI LITERATUR - Arvara Hudojo, Ghina Muthia; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2023)
ABSTRACT The glass ceiling phenomenon hinders the career development of women workers in construction indusrty. This study aims to provide a literature study related to motivational factors that can help overcome this phenomenon and cover the deficiencies of the literature which are the research gaps in this study. The research method uses a systematic literature study. The research data was obtained from internet searches regarding journals related to the glass ceiling phenomenon which were published from 2001-2023 with the keywords glass ceiling phenomenon, equity motivation theory, female workers in the construction industry, and barriers to career development for women in the construction industry. The total journals analyzed were 25 journals. Data were analyzed qualitatively. The results of the study show that motivation can help female workers overcome barriers to careers caused by the glass ceiling phenomenon in the construction industry.